ZAT WARNA ALAM ALTERNATIFWARNA BATIK YANG MENARIK - Sunarya, I Ketut (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2012)
The purpose that wants to be reached in this research is finding colorcontraction that being appeared by various types of leafs on tenun sutera, sertananas, and katun with fixation by tawas. This research also wants to know thequality of the natural color with sun shine heat and soap washed.The approach that being used in this research is Research andDevelopment (R&D) with steps: (1) Define (Preface Study) that is about thematerial that going to be worked with. In this research is more on explanationsabout tenun, leafs, and other helper material; (2) Design that is design about thework phases that going to be done by preparing the tools as a fist phase; (3)Development that is working with the material as various types of leafs thatbeing the ready material as natural color with fixation by tawas.The result of the research said that: First from 75 types of leaf that wasbeing worked as the color of sutera, serat nanas, and katun with fixation bytawas founded different variety of colors, they are cream, dark yellow, yellow,light yellow, brown, light brown, green, moss green, and orange. The result ofthe enduring power of natural color in sutera is good, whether by soap washedtest or sun shine heat test. In this test there is no low score and this is proof thatthe enduring power of natural color absorption in sutera is very good. That is aswell as natural color on serat nanas. While there is variation that found in thequality of natural color on katun, they are low quality category is seen in soapwashed test in kates leaf, aponika, lengki, leresede, belimbing manis, remujung,sukun, mangsi-mangsian, mangkokan, makuto dewo, jarak kepyar, kupu-kupuleaf, pace, puring, akasia, leaf bunga terompet, nangka, jambu air, melinjo,adam eva, yodium and suji leaf. It's different from sunshine heat test showspretty good result. Both, the special characteristics that owned by natural coloris the color intensity is very calming to the cornea. Variation colors that close tothe soft color. In the near future development natural color that is pleasant,secure, and interesting will used as batik color alternative.